Rehabilitation of injuries in competitive swimmers - Kenal, K. A.; Knapp, L. D. (Sports Medicine, 1996)
Good technique, reasonable flexibility, and strengthening exercises to maintain joint integrity will go a long way to avoiding injury in swimmers.